Pengaruh Gratitude terhadap Well-Being pada Remaja di Pondok Yatim Assalaam Bandung - Yasmien Mumtaz; Agus Budiman (UNISBA Press, 2024)
Abstract. Well-being is important for adolescents to be able to help adolescents cope with the challenges of adaptation. Adolescence is a transitional period where there are physical or psychological changes that often cause problems. The role of the family is important for the development of adolescents. But, in fact, not all the lucky teens are, there are teens who have to live in an orphanage so that they grow up with the affection of an imperfect parent. The Orphanage Assalaam Bandung is one of the orphanages in Bandung. In addition to providing facilities, the orphanage has practices to realize visions and missions, such as religious education, softskill training, social upbuilding, physical training, and advancing the family. It makes teenagers feel grateful during their stay at the orphanage. They feel happy, engaged in activity, have good relationships with others, have meaning in life, can a goal or achievement. This research is intended to find out the influence of gratitude on well-being in teenagers in the Assalaam Bandung Orphanage. This research uses a quantitative approach. Analysis techniques used simple regression analysis techniques. The research is a population study with a total of 51 adolescent subjects. Data collection using a questionnaire based on the gratification theory of Emmons & Mccullough (2004) namely The Gratitude Questionnaire-six items (GQ-6) adapted by Qodariah (2019) and the well-being scale The Workplace PERMA Profiler from Butler & Kern (2016) adapted by Elfida et al., (2021) refers to the Seligman theory. (2011). The results of this study have an influence of gratitude on well-being of 16.9% in the teens of the Orphanage Assalaam Bandung. Abstrak. Well-being penting dimiliki remaja agar bisa membantu remaja dalam menghadapi tantangan yang akan datang secara adaptif. Remaja adalah masa transisi dimana adanya perubahan fisik ataupun psikologis yang sering menyebabkan masalah. Peran keluarga terlebih orang tua penting bagi perkembangan remaja. Tetapi, pada kenyataannya tidak semua remaja bernasib beruntung, ada remaja yang harus tinggal di panti asuhan sehingga tumbuh dengan kasih sayang orang tua yang tidak utuh. Pondok Yatim Assalaam Bandung merupakan salah satu panti asuhan di Bandung. Selain menyediakan fasilitas, panti asuhan ini memiliki pembiasaan untuk mewujudkan visi dan misi, seperti pembiasaan keagamaan, pelatihan softskill, pembinaan sosial, pelatihan fisik, serta mengedepankan kekeluargaan. Hal itu membuat remaja merasa bersyukur selama tinggal di panti asuhan. Mereka merasa senang, terlibat dalam aktifitas, memiliki hubungan yang baik dengan orang lain, memiliki makna hidup, bisa mencapai tujuan atau prestasi. Penelitian ini bermaksud untuk mengetahui pengaruh gratitude terhadap well-being pada remaja Pondok Yatim Assalaam Bandung. Penelitian ini menggunakan pendekatan kuantitatif. Teknik analisis yang dipakai teknik analisis regresi sederhana. Penelitian berbentuk studi populasi dengan subjek sejumlah 51 remaja. Pengumpulan data menggunakan kuesioner yang dilandaskan pada teori gratitude dari Emmons & Mccullough (2004) yaitu The Gratitude Questionnaire-six item (GQ-6) yang sudah diadaptasi oleh Qodariah (2019) dan skala well-being yaitu The Workplace PERMA Profiler dari Butler & Kern (2016) yang sudah diadaptasi oleh Elfida et al., (2021) merujuk pada teori Seligman (2011). Hasil penelitian ini terdapat pengaruh gratitude terhadap well-being sebesar 16.9% pada remaja Pondok Yatim Assalaam Bandung.